Crustacean species off the coast of Kıyıköy (Black Sea, Türkiye) with a new record - Özgen Özge; Açık Şermin (Oceanological and Hydrobiological Studies)
Examination of hard- and soft-bottom samples collected off the coast of Kıyıköy (Black Sea, Türkiye) using grabs, quadrats and trawls revealed a total of 39 crustaceans belonging to eight orders. Among the species, Medorippe lanata was recorded in the Black Sea for the first time. Amphipoda dominated on hard and soft substrates in terms of the number of species and individuals. A total of 898 individuals belonging to 27 species were identified on the hard bottom, of which Ampithoe ramondi was the most dominant species (47.4%). On the other hand, a total of 123 individuals belonging to 16 species were recorded on the soft bottom, with Diogenes pugilator (21.1%) being the most dominant species (21.1%). A total of 441 individuals belonging to nine species were found following bottom and beam trawl hauls, with Liocarcinus navigator and L. depurator being the most frequent species. Community parameters were estimated in both hard- and soft-bottom samples.